Frieda - Millar, Ronald 1919-1998; Greenwood, John 1889-1975 (Studiocanal Limited, 2022)
"Frieda is a 1947 war drama directed by Basil Dearden and starring David Farrar, Glynis Johns, Flora Robson, Albert Lieven and Mai Zetterling. Frieda, a German girl, helps English Robert to escape from a German prisoner-of-war camp and in return he marries her so she can obtain a British passport even though he doesn't lover her. When returning to Robert's small English hometown, Frieda is met with hostile anti-German sentiment which is only worsened when her brother, a former Nazi and now Polish soldier arrives. What follows is a terrible awakening for Frieda who, deeply in love with her husband, cannot accept when Robert turns against her." [filmdienst.de]
Original: Großbritannien 1947
Extras: "Strength and weakness: Matthew Sweet on 'Frieda'" ; looking back at "Frieda" ; behind the scenes stills gallery
Bildformat 1.37:1
Keywords: Film; DVD-Video